2010
DOI: 10.1051/ocl.2010.0301
|View full text |Cite
|
Sign up to set email alerts
|

Détection de contaminants dans les huiles végétales : bilan à fin 2009

Abstract: The research of contaminants is part of multiple controls conducted by fat and oil industry to verify the conformity of products placed on the market in relation to regulations as for instance the commission regulation EC n o 1881/2006 setting maximum levels for some contaminants in food as lead, some mycotoxins, dioxins, polychlorobiphenyls, benzo [a]pyrene. In the absence of regulation, the detection of contaminants must be addressed in partnership with authorities according to the toxicity of molecules. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…Few publications (Neukom et al, 2002;Reich et al, 1997;Wagner et al, 2001;Moret et al, 2003) dealing with occurrence of oil hydrocarbon reported contents varying from few A103, page 4 of 9 F. Lacoste: OCL 2014, 21 (1) A103 milligrams per kilo to approximately 100 mg/kg in vegetable oils (Lacoste et al, 2010).…”
Section: Mineral Oil Detected In Vegetable Oilsmentioning
confidence: 99%
“…Few publications (Neukom et al, 2002;Reich et al, 1997;Wagner et al, 2001;Moret et al, 2003) dealing with occurrence of oil hydrocarbon reported contents varying from few A103, page 4 of 9 F. Lacoste: OCL 2014, 21 (1) A103 milligrams per kilo to approximately 100 mg/kg in vegetable oils (Lacoste et al, 2010).…”
Section: Mineral Oil Detected In Vegetable Oilsmentioning
confidence: 99%
“…Les quelques r esultats collect es via le PSO confirment la faible contamination des huiles raffin ees de colza et tournesol. A la suite d'une contamination d'huiles brutes de tournesol en provenance d'Ukraine par des huiles min erales (Lacoste, 2010), les industriels ont mis en place depuis 2008 une v erification syst ematique des huiles de tournesol d'importation. Les donn ees collect ees dans le cadre du PSO permettent de v erifier que cette contamination de 2008 etait un cas isol e.…”
Section: Un Contaminant Aunclassified
“…Le sujet est tres important et vaste ; nous renvoyons a deux articles (Lacoste, 2010 ;Pages et al, 2010) Un developpement tres interessant et inedit est notamment expose a partir d'une etude economique comparant, pour les trois types de tourteaux realisables industriellement, les prix d'interêt au-dela desquels l'incorporation de la matiere testee n'est plus possible. Sont precises les verrous a surmonter pour developper certaines opportunites : les auteurs soulignent la necessite de conduire des etudes economiques integrant l'impact des niveaux de prix du tourteau de soja et des deux cereales dominantes (ble et maïs).…”
Section: Maîtrise Des Contaminantsunclassified